Swimming Education and Water Safety in Schools: A Systematic Literature Review - Frekdi Alosius Manik; Jiyad Hawari; Suprayitno Suprayitno; Muhammad Yan (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose: This systematic literature review aims to synthesize global evidence on swimming education and water safety programs implemented within school settings, with particular emphasis on identifying effective pedagogical approaches, intervention frameworks, program characteristics, contextual facilitators, and persistent barriers that influence student swimming competency and drowning prevention outcomes. Materials and Methods: A systematic literature review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines. Five major academic databases were searched: Scopus, Web of Science, ERIC, PubMed, and ScienceDirect. Search strategies employed Boolean operators combining terms related to swimming instruction, aquatic education, water safety, drowning prevention, and school-based interventions. The review encompassed peer-reviewed journal articles published between 2019 and 2026, written in English. A total of 1,247 records were initially identified; following removal of duplicates, title and abstract screening, and full-text eligibility assessment, 52 studies met the inclusion criteria. Study quality was evaluated using the Critical Appraisal Skills Programme (CASP) and the Mixed Methods Appraisal Tool (MMAT). Thematic synthesis and narrative analysis were applied to extract and integrate key findings. Results: Five major thematic clusters emerged from the review: (1) structured aquatic curriculum models and their effectiveness across age groups; (2) instructional strategies and differentiated teaching in school-based swimming programs; (3) the role of water safety education in drowning prevention; (4) barriers to participation including socioeconomic disparities, cultural attitudes, facility access, and fear; and (5) the integration of technology and innovative pedagogies in aquatic education. Findings indicate that well-structured, age-appropriate, and culturally responsive swimming programs significantly improve fundamental aquatic skills and water safety knowledge among school-aged children. Nevertheless, critical inequities in program access persist globally. Conclusions: Swimming education and water safety represent an urgent public health imperative and an underinvested component of school physical education curricula globally. This review underscores the need for equitable, evidence-based aquatic education policies, adequately trained instructors, accessible facilities, and culturally sensitive program delivery. Future research should prioritize longitudinal effectiveness studies, equity-focused interventions, and the development of internationally standardized competency frameworks.